2015
DOI: 10.3389/fpsyt.2015.00063
|View full text |Cite
|
Sign up to set email alerts
|

A Parietal Biomarker for ADHD Liability: As Predicted by the Distributed Effects Perspective Model of ADHD

Abstract: BackgroundWe previously hypothesized that poor task-directed sensory information processing should be indexed by increased weighting of right hemisphere (RH) biased attention and visuo-perceptual brain functions during task operations and have demonstrated this phenotype in ADHD across multiple studies, using multiple methodologies. However, in our recent distributed effects model of ADHD, we surmised that this phenotype is not ADHD specific, but rather more broadly reflective of any circumstance that disrupts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 146 publications
(161 reference statements)
0
7
0
Order By: Relevance
“…Moreover, an abnormal hemispheric asymmetry of brain structure and function was also consistently reported in ADHD (Dennis and Thompson, 2013;Shang et al, 2013;Cao et al, 2014;Hale et al, 2014Hale et al, , 2015Keune et al, 2015;Silk et al, 2015), suggesting a possible neurodevelopmental scenario for this disorder.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Moreover, an abnormal hemispheric asymmetry of brain structure and function was also consistently reported in ADHD (Dennis and Thompson, 2013;Shang et al, 2013;Cao et al, 2014;Hale et al, 2014Hale et al, , 2015Keune et al, 2015;Silk et al, 2015), suggesting a possible neurodevelopmental scenario for this disorder.…”
Section: Introductionmentioning
confidence: 61%
“…Based on previous reports of abnormal laterality of the ADHD brain (Dennis and Thompson, 2013;Shang et al, 2013;Cao et al, 2014;Hale et al, 2014Hale et al, , 2015Keune et al, 2015;Silk et al, 2015), we could postulate that the asymmetric expression of neurodevelopmental genes might be at the origin of structural and functional changes in this disorder. However, these changes are not clear yet, as both a dysfunctional activity of the right hemisphere (Vance et al, 2007;Smith et al, 2008;Chamberlain et al, 2009;Bush, 2011) and the opposite (Cao et al, 2014;Hale et al, 2014Hale et al, , 2015 have been reported in literature. Moreover, the reflections of these unilateral activation deficits on functional connectivity are not trivial and require dedicated analyses focused on network properties (Dennis and Thompson, 2013;Cao et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
“…In ADHD, early lesion studies suggested a role for unilateral right hemisphere dysfunction ( Heilman and Van Den Abell, 1980 ; Stefanatos and Wasserstein, 2001 ). Previous studies have investigated aspects of structural brain symmetry in ADHD ( Rubia et al, 2000 ; Hale et al, 2015 ; Shaw et al, 2009a ). One of these studies reported increased asymmetry in the TD group, using homologous points on the cortex for comparison ( Shaw et al, 2009a ).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have suggested that the DMN is not altered at rest but in the transition from rest to task [ 15 ]. Abnormalities in the DMN are also evident in structural-functional right-based DMN asymmetry [ 10 , 16 ]. Increased or atypical functional asymmetry and abnormal interhemispheric processing in ADHD have also been reported by Fassbender and Schweitzer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%